High-temperature-resistant and flame-retardant artificial stone plate as well as preparation method and application thereof
By using silicon-containing aromatic or heterocyclic modified epoxy resins and composite flame retardants in artificial stones, the problem of insufficient heat resistance and flame retardant performance of existing artificial stones under high temperature conditions is solved, and higher heat resistance and flame retardant performance is achieved, which extends the application range and improves safety.
Patent Information
- Application Number
- CN202411734758.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
The existing artificial stone materials have insufficient heat resistance and flame retardant properties under high temperature conditions, which limits their application range.
Silicon-containing aromatic or heterocyclic modified epoxy resin is used as the binder, and combined with silica sand, specific curing agents and compound flame retardants (reactive flame retardants and filler flame retardants) to increase the thermal deformation temperature and initial thermal decomposition temperature of artificial stone.
The heat resistance and flame retardant properties of artificial stone are significantly improved, making its thermal deformation temperature reach above 200℃ and its initial thermal decomposition temperature reach above 340℃, which expands its application range and improves safety during use.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of artificial stones, and in particular relates to a high temperature resistant and flame retardant artificial stone plate and a preparation method and application thereof. Background Art
[0002] At present, artificial stone basically uses resin as a binder, and its heat resistance and flame retardancy need to be further improved, which limits its scope of use. The test conditions for heat resistance of solid surface materials and quartz stone in the test standard "JC / T 908-2013 Artificial Stone" are 185±5℃ aluminum plate contact for 10±0.5min; the high temperature resistance test conditions for solid surface materials are 180±1℃ bath wax pot contact for 20min. The temperature conditions of this heat resistance test cannot meet many scenarios of artificial stone application.
[0003] A study disclosed a highly flame-retardant artificial quartz stone plate, which improved its flame retardant properties by adding zinc borate and the like. A study disclosed a highly flame-retardant artificial quartz stone plate, which added hydroxide as a flame retardant to improve its flame retardant properties. A study disclosed the use of unsaturated polyester as an adhesive to prepare a flame-retardant artificial quartz stone plate. Although the flame retardant properties can be improved to a certain extent by adding an external flame retardant, the heat resistance of the resin in the artificial stone under high temperature conditions is not taken into account. The heat deformation temperatures of the unsaturated resin and polymethyl methacrylate resin commonly used in artificial stone are 50-60°C and 85-100°C, and the initial thermal decomposition temperatures are 200°C and 220°C, respectively, with poor heat resistance, that is, artificial stone cannot take into account both flame retardant properties and heat resistance.
[0004] Therefore, it is of great significance to provide an artificial stone plate with good flame retardancy and heat resistance. Summary of the invention
[0005] The present invention aims to solve one or more technical problems existing in the above-mentioned prior art and at least provide a beneficial choice. Specifically, the present invention provides an artificial stone board which has good flame retardancy and heat resistance.
[0006] The inventive concept of the present invention is as follows: the artificial stone board of the present invention comprises epoxy resin, silica sand, curing agent, filler, flame retardant A and flame retardant B; the epoxy resin comprises epoxy resin modified by silicon-containing aromatic ring or heterocyclic ring; the curing agent comprises at least one of aromatic amine curing agent, polyamide curing agent, acid anhydride curing agent and isocyanate curing agent; the flame retardant A comprises bromine-containing compound; the flame retardant B comprises at least one of halide, trihydrated aluminum oxide and antimony trioxide. The present invention uses epoxy resin modified by silicon-containing aromatic ring or heterocyclic ring as adhesive, silica sand as aggregate, and combines a specific type of curing agent and a composite flame retardant (flame retardant A is a reactive flame retardant, and flame retardant B is a filler flame retardant). The components work together to make the thermal deformation temperature of the artificial stone above 200°C and the initial thermal decomposition temperature above 340°C. It has good heat resistance and flame retardant properties, which can greatly expand the application range of artificial stone and improve the safety of artificial stone board during use.
[0007] Therefore, a first aspect of the present invention provides a high temperature resistant and flame retardant artificial stone board.
[0008] Specifically, the high temperature resistant and flame retardant artificial stone plate comprises epoxy resin, silica sand, curing agent, filler, flame retardant A and flame retardant B;
[0009] The epoxy resin includes an epoxy resin modified by a silicon-containing aromatic ring or a heterocyclic ring;
[0010] The curing agent includes at least one of an aromatic amine curing agent, a polyamide curing agent, an acid anhydride curing agent, and an isocyanate curing agent;
[0011] The flame retardant A comprises a bromine-containing compound;
[0012] The flame retardant B includes at least one of halides, aluminum trihydrate, and antimony trioxide.
[0013] Preferably, the bromine-containing compound includes at least one of decabromodiphenyl ethane, decabromodiphenyl ether, hexabromocyclododecane, octabromoether and tetrabromobisphenol A.
[0014] Preferably, the halogenated compound comprises at least one of tetrachlorophthalic anhydride, tetrachlorobisphenol A, hexachlorocyclopentene, bis(hexachlorocyclopentadiene)cyclooctane, perchlorocyclopentadecane and tetrachlorophthalic anhydride.
[0015] Preferably, the aromatic amine curing agent includes 3-anilinopropyltrimethoxysilane.
[0016] Specifically, by adding 3-anilinopropyltrimethoxysilane, a silicon-containing reactive curing agent, a high-temperature resistant rigid group is introduced during the cross-linking and curing process of the epoxy resin to improve the high-temperature resistance.
[0017] Preferably, the artificial stone plate comprises, by weight, 90-130 parts of epoxy resin, 300-500 parts of silica sand, 55-100 parts of curing agent, 9-55 parts of filler, 18-38 parts of flame retardant A, and 11-85 parts of flame retardant B.
[0018] Further preferably, the artificial stone board comprises, by weight, 100-120 parts of epoxy resin, 320-460 parts of silica sand, 60-90 parts of curing agent, 10-50 parts of filler, 20-35 parts of flame retardant A, and 12-82 parts of flame retardant B.
[0019] Preferably, the artificial stone plate further comprises at least one of an accelerator and a pigment.
[0020] Preferably, the artificial stone board also includes an accelerator and a pigment, and by weight, the artificial stone board includes 90-130 parts of epoxy resin, 300-500 parts of silica sand, 55-100 parts of curing agent, 9-55 parts of filler, 18-38 parts of flame retardant A, 11-85 parts of flame retardant B, greater than 0 parts and less than or equal to 3.3 parts of accelerator, and greater than 0 parts and less than or equal to 10 parts of pigment.
[0021] Further preferably, the artificial stone board also includes an accelerator and a pigment, and by weight, the artificial stone board includes 100-120 parts of epoxy resin, 320-460 parts of silica sand, 60-90 parts of curing agent, 10-50 parts of filler, 20-35 parts of flame retardant A, 12-82 parts of flame retardant B, greater than 0 parts and less than or equal to 3 parts of accelerator, and greater than 0 parts and less than or equal to 6.5 parts of pigment.
[0022] Preferably, the SiO2 content in the silica sand is above 95%.
[0023] Preferably, the particle size of the silica sand is 0.15-9 mm; further preferably, the particle size of the silica sand is 0.2-8.0 mm.
[0024] Preferably, the filler is an active filler.
[0025] Preferably, the particle size of the filler is 9-110 nm; more preferably, the particle size of the filler is 10-100 nm.
[0026] Preferably, the filler includes at least one of SiO2, TiO2, Al2O3, CaCO3, and ZnO.
[0027] Specifically, the filler is active inorganic particles.
[0028] Preferably, the accelerator comprises an imidazole compound.
[0029] The second aspect of the present invention provides a method for preparing the artificial stone slab according to the first aspect of the present invention.
[0030] Specifically, the method for preparing the artificial stone plate comprises the following steps:
[0031] The raw material components are mixed, molded and cured to obtain the artificial stone plate.
[0032] Preferably, the method for preparing the artificial stone plate comprises the following steps:
[0033] (1) mixing the epoxy resin, flame retardant A, flame retardant B, and pigment, and stirring at high speed; then adding a curing agent and an accelerator and mixing evenly to obtain a slurry;
[0034] (2) adding the silica sand into a mixer, stirring for the first time, then adding the slurry obtained in step (1), stirring for the second time, and finally adding the remaining components, stirring for the third time to obtain a mixture;
[0035] (3) placing the mixture obtained in step (2) into a molding mold, evacuating the mixture, vibrating and pressing the mixture, and curing the mixture to obtain the artificial stone plate.
[0036] Preferably, in step (1), the high-speed stirring time is 9-22 min; further preferably, in step (1), the high-speed stirring time is 10-20 min.
[0037] Preferably, in step (1), the stirring conditions for the high-speed stirring are: forward rotation and reverse rotation for 1-2 minutes each, alternating, and first stirring at a speed of 300-500 rpm for 3-5 min, and stirring at 800-1000 rpm for the remaining time.
[0038] Preferably, in step (2), the conditions for the first stirring, the second stirring and the third stirring are that the forward rotation and the reverse rotation are respectively rotated for 60-80 seconds in sequence, and the stirring speed is 18-33 Hz.
[0039] Further preferably, in step (2), the conditions for the first stirring, the second stirring, and the third stirring are all to rotate forward and reverse for 55-75 seconds in sequence, alternately, and the stirring speed is 20-30 Hz.
[0040] Preferably, in step (2), during the first stirring, the time for both forward and reverse rotation is 1-3 min.
[0041] Preferably, in step (2), during the second stirring, the time for both forward and reverse rotation is 3-5 min.
[0042] Preferably, in step (2), during the third stirring, the time for both forward and reverse rotation is 2-5 min.
[0043] Preferably, in step (3), the vacuum degree of the vacuum pumping is less than or equal to -0.090 MPa, and the vacuum pumping time is 80-130 s; further preferably, in step (3), the vacuum degree of the vacuum pumping is less than or equal to -0.092 MPa, and the vacuum pumping time is 90-120 s.
[0044] Preferably, vacuum is maintained during the vibration compression molding process.
[0045] Preferably, in step (3), the vibration frequency of the vibration compression molding is 38-50 Hz; further preferably, in step (3), the vibration frequency of the vibration compression molding is 42-45 Hz.
[0046] Preferably, the molding pressure of the vibration molding is divided into 6 sections: the molding pressure of the first section is 27-38MPa, and the holding time is 12-18s, the molding pressure of the second section is 32-42MPa, and the holding time is 12-18s, the molding pressure of the third section is 35-45MPa, and the holding time is 16-25s, the molding pressure of the fourth section is 38-48MPa, and the holding time is 32-50s, the molding pressure of the fifth section is 43-55MPa, and the holding time is 16-25s, and the molding pressure of the sixth section is 30-38MPa, and the holding time is 8-12s.
[0047] Further preferably, the molding pressure of the compression molding is divided into 6 sections: the molding pressure of the first section is 30-35MPa, and the holding time is 13-16s, the molding pressure of the second section is 36-38MPa, and the holding time is 13-16s, the molding pressure of the third section is 40-41MPa, and the holding time is 18-22s, the molding pressure of the fourth section is 42-44MPa, and the holding time is 35-45s, the molding pressure of the fifth section is 48-50MPa, and the holding time is 18-22s, and the molding pressure of the sixth section is 33-35MPa, and the holding time is 9-11s.
[0048] Preferably, the curing is firstly kept at 90-110° C. for 0.9-3.5 h, and then kept at 140-190° C. for 2.5-5.5 h.
[0049] Further preferably, the curing is firstly kept at 90-100° C. for 1-3 hours, and then kept at 150-180° C. for 3-5 hours.
[0050] Specifically, the curing furnace used for the curing is divided into three areas, two heating areas and one cooling area. The temperatures of the two heating areas are 90-110°C and 140-190°C respectively, and the temperature of the cooling area is 80-90°C.
[0051] Preferably, the curing process also includes demoulding, grinding and polishing.
[0052] The third aspect of the present invention provides an application of the artificial stone board described in the first aspect of the present invention in the field of construction.
[0053] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0054] (1) The present invention uses an epoxy resin modified with a silicon-containing aromatic ring or heterocyclic ring as a binder, uses silica sand as an aggregate, and combines a specific type of curing agent, a reactive flame retardant, and a filler flame retardant. The components work together to make the artificial stone have a thermal deformation temperature of more than 200°C and an initial thermal decomposition temperature of more than 340°C. The artificial stone has good heat resistance and flame retardancy, which can greatly expand the application range of the artificial stone and improve the safety of the artificial stone board during use.
[0055] (2) The present invention introduces flame retardant groups during the crosslinking and curing process of epoxy resin by adding a reactive flame retardant, and uses a filler flame retardant in combination to synergistically improve the flame retardant effect. By adding a silicon-containing reactive curing agent 3-anilinopropyltrimethoxysilane, a high-temperature resistant rigid group is introduced during the crosslinking and curing process of epoxy resin to improve the high temperature resistance. DETAILED DESCRIPTION
[0056] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0057] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0058] Example 1
[0059] A high temperature resistant and flame retardant artificial stone plate, which comprises, by weight, 100 parts of epoxy resin (organic silicon modified bisphenol A epoxy resin EPSI-3201 produced by Jining Zhongjian Chemical Company), 430 parts of 40-70 mesh silica sand, 90 parts of 3-anilinopropyltrimethoxysilane curing agent, 2.5 parts of 2-undecylimidazole accelerator, 50 parts of active silicon dioxide, 25 parts of decabromodiphenylethane, 16 parts of antimony trioxide and 1.6 parts of titanium dioxide.
[0060] A method for preparing a high temperature resistant and flame retardant artificial stone plate comprises the following steps:
[0061] (1) Weigh each raw material according to the formula, and the weighing error range is within ±0.2%;
[0062] (2) Mix epoxy resin, halogen flame retardant, antimony trioxide and titanium dioxide and stir at high speed for 20 minutes (stirring conditions are forward and reverse rotation for 1 minute, alternately, stirring at a stirring speed of 400 r / min for 3 minutes, and the stirring speed for the remaining time is 900 r / min); then add 3-anilinopropyltrimethoxysilane curing agent and 2-undecylimidazole accelerator and stir evenly to obtain slurry;
[0063] (3) Add silica sand into the mixer and stir for 3 min (stirring conditions are forward and reverse rotation for 60 seconds, alternately, and stirring speed is 25 Hz); then add the slurry obtained in step (1) and stir for 5 min (stirring conditions are forward and reverse rotation for 60 seconds, alternately, and stirring speed is 25 Hz); finally add the remaining raw material components and stir for 5 min (stirring conditions are forward and reverse rotation for 60 seconds, alternately, and stirring speed is 25 Hz) to obtain a mixture;
[0064] (4) placing the mixture obtained in step (3) into a molding mold, evacuating the mixture for 120 seconds at a vacuum degree below -0.092 MPa, maintaining the vacuum and starting vibration compression molding, the vibration frequency is 43 Hz, and the compression molding pressure is divided into 6 stages, the first stage compression pressure is 35 MPa, the pressure is maintained for 15 seconds, the second stage compression pressure is 38 MPa, the pressure is maintained for 15 seconds, the third stage compression pressure is 41 MPa, the pressure is maintained for 20 seconds, the fourth stage compression pressure is 44 MPa, the pressure is maintained for 40 seconds, the fifth stage compression pressure is 50 MPa, the pressure is maintained for 20 seconds, and the sixth stage compression pressure is 35 MPa, the pressure is maintained for 10 seconds; then curing in a curing furnace, first at 90°C for 2 hours, then at 180°C for 3 hours, and then at 80°C for 3 hours, naturally cooling to room temperature, demolding, cooling, grinding and polishing after curing to obtain an artificial stone slab.
[0065] Example 2
[0066] A high temperature resistant and flame retardant artificial stone plate comprises, by weight, 120 parts of epoxy resin (organic silicon modified bisphenol A epoxy resin EPSI-3201 produced by Jining Zhongjian Chemical Company), 380 parts of 70-120 mesh silica sand, 80 parts of 3-anilinopropyltrimethoxysilane curing agent, 2 parts of 2-undecylimidazole accelerator, 10 parts of active silicon dioxide, 60 parts of alumina trihydrate (ATH), 30 parts of tetrabromobisphenol A, 20 parts of antimony trioxide, 2 parts of titanium dioxide and 4.5 parts of yellow iron oxide.
[0067] A method for preparing a high temperature resistant and flame retardant artificial stone plate comprises the following steps:
[0068] (1) Weigh each raw material according to the formula, and the weighing error range is within ±0.2%;
[0069] (2) Mix epoxy resin, halogen flame retardant, antimony trioxide, titanium dioxide, and yellow iron oxide and stir at high speed for 20 minutes (stirring conditions are forward and reverse rotation for 1 minute, alternately, stirring at a stirring speed of 400 r / min for 3 minutes, and the stirring speed for the remaining time is 900 r / min); then add 3-anilinopropyltrimethoxysilane curing agent and 2-undecylimidazole accelerator and stir evenly to obtain a slurry;
[0070] (3) Add silica sand into the mixer and stir for 3 min (stirring conditions are forward and reverse rotation for 60 seconds, alternately, and stirring speed is 25 Hz); then add the slurry obtained in step (1) and stir for 5 min (stirring conditions are forward and reverse rotation for 60 seconds, alternately, and stirring speed is 25 Hz); finally add the remaining raw material components and stir for 5 min (stirring conditions are forward and reverse rotation for 60 seconds, alternately, and stirring speed is 25 Hz) to obtain a mixture;
[0071] (4) placing the mixture obtained in step (3) into a molding mold, and subjecting the mixture to a vacuum degree of less than -0.092 MPa for 120 seconds, while maintaining the vacuum and starting vibration compression molding, the vibration frequency is 42-45 Hz, and the compression molding pressure is divided into 6 stages, the first stage compression pressure is 35 MPa, and the pressure is maintained for 15 seconds, the second stage compression pressure is 38 MPa, and the pressure is maintained for 15 seconds, the third stage compression pressure is 41 MPa, and the pressure is maintained for 20 seconds, the fourth stage compression pressure is 44 MPa, and the pressure is maintained for 40 seconds, the fifth stage compression pressure is 50 MPa, and the pressure is maintained for 20 seconds, and the sixth stage compression pressure is 35 MPa, and the pressure is maintained for 10 seconds; then curing in a curing furnace, first at 90°C for 2 hours, then at 180°C for 3 hours, and then at 80°C for 3 hours, and naturally cooling to room temperature. After curing, demolding, cooling, grinding, and polishing are performed to obtain an artificial stone slab.
[0072] Example 3
[0073] A high temperature resistant and flame retardant artificial stone plate, comprising, by weight, 110 parts of epoxy resin (organic silicon modified bisphenol A epoxy resin EPSI-3201 produced by Jining Zhongjian Chemical Company), 160 parts of 40-110 mesh silica sand, 300 parts of 16-26 mesh silica sand, 80 parts of 3-anilinopropyltrimethoxysilane curing agent, 2 parts of 2-undecylimidazole accelerator, 10 parts of activated calcium carbonate, 70 parts of ATH, 25 parts of hexabromocyclododecane and 3.5 parts of black iron oxide.
[0074] A method for preparing a high temperature resistant and flame retardant artificial stone plate comprises the following steps:
[0075] (1) Weigh each raw material according to the formula, and the weighing error range is within ±0.2%;
[0076] (2) Mix epoxy resin, halogen flame retardant, ATH, and black iron oxide and stir at high speed for 20 minutes (stirring conditions are forward and reverse rotation for 1 minute, alternately, stirring at a stirring speed of 400 r / min for 3 minutes, and the stirring speed for the remaining time is 900 r / min); then add 3-anilinopropyltrimethoxysilane curing agent and 2-undecylimidazole accelerator and stir evenly to obtain a slurry;
[0077] (3) Add silica sand into the mixer and stir for 3 min (stirring conditions are forward and reverse rotation for 60 seconds, alternately, and stirring speed is 25 Hz); then add the slurry obtained in step (1) and stir for 5 min (stirring conditions are forward and reverse rotation for 60 seconds, alternately, and stirring speed is 25 Hz); finally add the remaining raw material components and stir for 5 min (stirring conditions are forward and reverse rotation for 60 seconds, alternately, and stirring speed is 25 Hz) to obtain a mixture;
[0078] (4) placing the mixture obtained in step (3) into a molding mold, and subjecting the mixture to a vacuum degree of less than -0.092 MPa for 120 seconds, while maintaining the vacuum and starting vibration compression molding, the vibration frequency is 42-45 Hz, and the compression molding pressure is divided into 6 stages, the first stage compression pressure is 35 MPa, and the pressure is maintained for 15 seconds, the second stage compression pressure is 38 MPa, and the pressure is maintained for 15 seconds, the third stage compression pressure is 41 MPa, and the pressure is maintained for 20 seconds, the fourth stage compression pressure is 44 MPa, and the pressure is maintained for 40 seconds, the fifth stage compression pressure is 50 MPa, and the pressure is maintained for 20 seconds, and the sixth stage compression pressure is 35 MPa, and the pressure is maintained for 10 seconds; then curing in a curing furnace, first at 90°C for 2 hours, then at 180°C for 3 hours, and then at 80°C for 3 hours, and naturally cooling to room temperature. After curing, demolding, cooling, grinding, and polishing are performed to obtain an artificial stone slab.
[0079] Comparative Example 1
[0080] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses an equal amount of the phosphorus-containing compound ditolyl phosphate to replace the halogen-based flame retardant, and the rest is the same as Example 1.
[0081] Comparative Example 2
[0082] The difference between Comparative Example 2 and Example 1 is that an equal amount of magnesium oxide is used in Comparative Example 2 to replace antimony trioxide, and the rest is the same as Example 1.
[0083] Comparative Example 3
[0084] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 uses an equal amount of triethanolamine curing agent to replace 3-anilinopropyltrimethoxysilane curing agent, and the rest is the same as Example 1.
[0085] Comparative Example 4
[0086] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 uses an equal amount of bisphenol A epoxy resin agent to replace the silicone-modified bisphenol A epoxy resin, and the rest is the same as Example 1.
[0087] Performance Testing
[0088] The performance tests were conducted on the artificial stone panels of Examples 1-3 and Comparative Examples 1-4. The test items and test methods are as follows:
[0089] Oxygen index: Determined in accordance with GB / T 2406.2 Plastics Oxygen Index Method for Determination of Combustion Behavior Part 2: Room Temperature Test;
[0090] Heat deformation temperature: measured in accordance with GB / T 1634.1-2004 Determination of load deformation temperature of plastics;
[0091] Thermal decomposition temperature: Determined in accordance with GB / T 37631-2019 Test method for thermal decomposition temperature of chemical fibers.
[0092] The performance test results of the artificial stone panels of Examples 1-3 and Comparative Examples 1-4 are shown in Table 1.
[0093] Table 1: Test results of artificial stone slab performance of Examples 1-3 and Comparative Examples 1-4
[0094] Group Oxygen Index Heat deformation temperature / ℃ Initial thermal decomposition temperature / ℃ Example 1 42.3 225 345 Example 2 43.2 230 352 Example 3 40.5 200 340 Comparative Example 1 35.4 132 190 Comparative Example 2 33.8 130 185 Comparative Example 3 34.2 120 180 Comparative Example 4 34.6 145 186
[0095] It can be seen from Table 1 that the artificial stone board prepared by the present invention has a relatively high oxygen index, heat deformation temperature, and initial thermal decomposition temperature, that is, the artificial stone board is resistant to high temperatures and has good flame retardancy.
[0096] Comparative Example 1 uses an equal amount of phosphorus-containing compounds to replace the halogen flame retardant, so that the oxygen index, heat deformation temperature, and initial thermal decomposition temperature of the artificial stone board of Comparative Example 1 are significantly lower than those of Example 1. Comparative Example 2 uses an equal amount of aluminum oxide to replace antimony trioxide, so that the oxygen index, heat deformation temperature, and initial thermal decomposition temperature of the artificial stone board of Comparative Example 2 are significantly lower than those of Example 1. Comparative Example 3 uses an equal amount of triethanolamine curing agent to replace 3-anilinopropyltrimethoxysilane curing agent, so that the oxygen index, heat deformation temperature, and initial thermal decomposition temperature of the artificial stone board of Comparative Example 3 are significantly lower than those of Example 1. It shows that only when a specific type of reactive flame retardant and filler flame retardant are compounded and a specific type of curing agent is used can the artificial stone board have good high temperature resistance and flame retardant effect. Comparative Example 4 uses an equal amount of bisphenol A epoxy resin to replace silicone-modified bisphenol A epoxy resin, so that the oxygen index, heat deformation temperature, and initial thermal decomposition temperature of the artificial stone board of Comparative Example 4 are significantly lower than those of Example 1. It shows that silicone-modified epoxy resin can make the artificial stone board have good high temperature resistance and flame retardant effect.
[0097] In summary, the present invention adopts a specific type of curing agent and a compound of a reactive flame retardant and a filler flame retardant. The components work together to make the artificial stone have an oxygen index greater than 40, a thermal deformation temperature above 200°C, and an initial thermal decomposition temperature above 340°C. It has good heat resistance and flame retardant properties, can greatly expand the application range of artificial stone, and improve the safety of artificial stone panels during use.
[0098] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An artificial stone plate, characterized in that: Including epoxy resin, silica sand, curing agent, filler, flame retardant A and flame retardant B; The epoxy resin includes an epoxy resin modified by a silicon-containing aromatic ring or a heterocyclic ring; The curing agent includes at least one of an aromatic amine curing agent, a polyamide curing agent, an acid anhydride curing agent, and an isocyanate curing agent; The flame retardant A comprises a bromine-containing compound; The flame retardant B includes at least one of halides, aluminum trihydrate, and antimony trioxide.
2. The artificial stone plate according to claim 1, characterized in that: The bromine-containing compound includes at least one of decabromodiphenyl ethane, decabromodiphenyl ether, hexabromocyclododecane, octabromoether and tetrabromobisphenol A.
3. The artificial stone plate according to claim 1, characterized in that: The halogenated compound comprises at least one of tetrachlorophthalic anhydride, tetrachlorobisphenol A, hexachlorocyclopentene, bis(hexachlorocyclopentadiene)cyclooctane, perchlorocyclopentadecane and tetrachlorophthalic anhydride.
4. The artificial stone plate according to claim 1, characterized in that: The aromatic amine curing agent includes 3-anilinopropyltrimethoxysilane.
5. The artificial stone plate according to claim 1, characterized in that: Calculated by weight, the artificial stone plate includes 90-130 parts of epoxy resin, 300-500 parts of silica sand, 55-100 parts of curing agent, 9-55 parts of filler, 18-38 parts of flame retardant A, and 11-85 parts of flame retardant B.
6. The artificial stone plate according to claim 1, characterized in that: The artificial stone plate further comprises at least one of an accelerator and a pigment.
7. The artificial stone plate according to claim 6, characterized in that: The artificial stone board also includes an accelerator and a pigment, and by weight, the artificial stone board includes 90-130 parts of epoxy resin, 300-500 parts of silica sand, 55-100 parts of curing agent, 9-55 parts of filler, 18-38 parts of flame retardant A, 11-85 parts of flame retardant B, greater than 0 parts and less than or equal to 3.3 parts of the accelerator, and greater than 0 parts and less than or equal to 10 parts of the pigment.
8. The artificial stone plate according to claim 7, characterized in that: The particle size of the silica sand is 0.15-9 mm; and / or the particle size of the filler is 9-110 nm; and / or the filler includes at least one of SiO2, TiO2, Al2O3, CaCO3, and ZnO; and / or the promoter includes an imidazole compound.
9. The method for preparing the artificial stone plate according to any one of claims 1 to 8, characterized in that: The following steps are involved: The raw material components are mixed, molded and cured to obtain the artificial stone plate.
10. Use of the artificial stone board according to any one of claims 1 to 8 in the field of construction.